The Representation of Persians as Villains in a Movie ‘300’: An Analysis of Orientalism Perspective by Edward Said - Imam Maruf (Passage, 2014)
This paper investigates the ways the Persians are represented in the movie ‘300’. Furthermore, the study also analyzes the relationship between the movie and the current socio-political issues between the United States and Iran. This study uses Edward Said’s (1978) Orientalism as the main theoretical framework and Davis, Mules and Thwaites’ (1994) character and characterization as the supporting theoretical framework. In addition, Brian’s (2005) Film and Politicsin Americais used to to analyze the relationship between the movie ‘300’ and the socio-political issues between the U.S. and Iran. The study finds that Persians are characterized as being inferior, evil, savage, bestial, and corrupt,amplifying their positions as the villains in the movie. This negative portrayals, from a perspective of the Orientalist, areforms of pejorative stereotypes. With regard to the relationship between the movie and the current socio-political issue between the U.S. and Iran, it seems apparent that the movie is used asapropaganda by the U.S. government. This can be clearly seen from the negative representation of Persians as villains, the movie producer, and the time of the movie release. All the findings above indicate that a film can be used as a tool for a propaganda.Keywords: Orientalism, Orient, Occident, Character and Characterization, Representation, Persians